2000
DOI: 10.1074/jbc.275.14.9897
|View full text |Cite
|
Sign up to set email alerts
|

Agonists Trigger G Protein-mediated Activation of the CPI-17 Inhibitor Phosphoprotein of Myosin Light Chain Phosphatase to Enhance Vascular Smooth Muscle Contractility

Abstract: Myosin light chain phosphatase (MLCP) plays a pivotal role in smooth muscle contraction by regulating Ca2؉ sensitivity of myosin light chain phosphorylation. A smooth muscle phosphoprotein called CPI-17 specifically and potently inhibits MLCP in vitro and in situ and is activated when phosphorylated at Thr-38, which increases its inhibitory potency 1000-fold. We produced a phosphospecific antibody for this site in CPI-17 and used it to study in situ phosphorylation of endogenous CPI-17 in arterial smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
289
3
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 307 publications
(312 citation statements)
references
References 27 publications
11
289
3
2
Order By: Relevance
“…Most of the ROCK substrates are cellular proteins associated with the regulation of actin cytoskeleton. Besides MLC and MYPT1, this important subset of ROCK substrates include CPI-17 [63], calponin [58], LIM kinases [80,99,132], ezrin/radixin/moesin (ERM) [83], adducin [37], sodium-hydrogen exchanger (NHE1) [137] and ZIP kinase [43].…”
Section: Substrates Of Rockmentioning
confidence: 99%
“…Most of the ROCK substrates are cellular proteins associated with the regulation of actin cytoskeleton. Besides MLC and MYPT1, this important subset of ROCK substrates include CPI-17 [63], calponin [58], LIM kinases [80,99,132], ezrin/radixin/moesin (ERM) [83], adducin [37], sodium-hydrogen exchanger (NHE1) [137] and ZIP kinase [43].…”
Section: Substrates Of Rockmentioning
confidence: 99%
“…PKC acts by phosphorylating an endogenous 17 kDa inhibitory protein, PKC-activated 17 kDa inhibitor protein of type 1 phosphatase (CPI-17). Phosphorylation of CPI-17 greatly augments its ability to bind to the catalytic subunit of MLCP, causing inhibition of MLCP activity [24][25][26]. Although Rho kinase is capable of activating CPI-17 in vitro, albeit to a lesser extent when compared with PKC, its predominant effect in vivo appears to be via phosphorylation of the large, 110-130 kDa regulatory myosin phosphatase targeting subunit (MYPT1), and inhibition of MLCP activity [27].…”
Section: Phosphorylation Of Sermentioning
confidence: 99%
“…Hydrolysis of phosphatidylcholine by PLD yields phosphatidic acid, which is dephosphorylated to diacylglycerol, leading to sustained activation of various protein kinase C (PKC) isoenzymes. Rho kinase and PKC, either singly or co-operatively, are involved in the inhibition of MLCP [12][13][14][15][16][17][23][24][25][26]. PKC acts by phosphorylating an endogenous 17 kDa inhibitory protein, PKC-activated 17 kDa inhibitor protein of type 1 phosphatase (CPI-17).…”
Section: Phosphorylation Of Sermentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of Thr38 of CPI-17 increases over 10 3 -fold in inhibitory potency for MP [2]. CPI-17 is exclusively expressed in smooth muscle and brain [2], and suggested to function controlling vascular tone [3] and maintaining cerebellar memory [4]. A series of biochemical experiments suggested that this inhibition is achieved by the direct binding of phospho-Thr38 on CPI-17 to the catalytic site of MP [5 -7].…”
Section: Introductionmentioning
confidence: 99%